Clinical characteristics and surgical outcomes of solitary spinal epidural cavernous angiomas - Yang, Tao (Oncol Lett, 2018)
The majority of spinal cavernous angiomas (CAs) originate from the vertebral bodies with or without epidural space extension. Solitary epidural CAs are rare. In the present study, we retrospectively reviewed the records of 12 patients who underwent microsurgery for solitary spinal epidural CAs. All patients had performed pre- and postoperative magnetic resonance imaging. The patients were 7 females and 5 males with the mean age of 52.1 years. Two tumors were located in the cervicothoracic spine, nine in the thoracic spine and one in the lumbar spine, respectively. Solitary epidural CAs generally exhibited isointensity on T1-weighted images and hyperintesity on T2-weighted images. Contrast-enhanced T1-weighted images showed homogeneous markedly enhancement. Gross total resection (GTR) was achieved in 11 cases, and subtotal resection (STR) was achieved in 1 case. During an average follow up of 35.9 months, neurological function was improved in 11 patients and in one patient, preoperative status was maintained. No patient experienced tumor recurrence. These findings suggest that CAs should be considered in the differential diagnosis of spinal epidural lesions. Early surgery is advocated to prevent irreversible neurological deficits. When aggravated by a large amount of acute hemorrhage, neurological deterioration is usually acute and prompt surgical decompression is the optimal choice. Because of the excessive vascularity of CAs, en bloc resection is recommended. In addition, a good clinical outcome after GTR can be expected, and the risk of long-term recurrence is low.